2019
DOI: 10.3136/fstr.25.123
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Polyphenols under Alkaline Conditions and the Formation of a Xanthine Oxidase Inhibitor from Gallic Acid in a Solution at pH 7.4

Abstract: The stability of 20 different types of polyphenols that are constituents of edible plants was evaluated under different pH conditions (in buffer solutions at pH 6.8, 7.4, and 8.3). Carnosol was the most unstable, followed by myricetin, quercetin, carnosic acid, nordihydroguaiaretic acid, baicalein, gallic acid, and hydroxytyrosol. They were more unstable at a higher pH, which may be attributed to their enhanced redox properties in alkaline solutions, determined by their antioxidant and prooxidant activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…One report demonstrated that when this process is carried out at pH 7.4, a o -quinone is produced and changes in the solution’s absorbance spectra can be observed 26 . In another instance, incubation of GA at neutral pH lead to the formation of a gallic acid dimer 30 . Oxidation at highly basic conditions was shown to yield ellagic acid 31 .…”
Section: Introductionmentioning
confidence: 99%
“…One report demonstrated that when this process is carried out at pH 7.4, a o -quinone is produced and changes in the solution’s absorbance spectra can be observed 26 . In another instance, incubation of GA at neutral pH lead to the formation of a gallic acid dimer 30 . Oxidation at highly basic conditions was shown to yield ellagic acid 31 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the incorporation of mango peel PC into food products represents a challenge due to their susceptibility to oxidative reactions during processing conditions (pH, time, temperature, oxygen availability) and unpleasant taste (such as bitterness and astringency). In addition, a number of studies have shown that PC extracts are susceptible to oxidation at physiological intestinal pH (∼ 6.0-7.5), limiting their bioavailability and potential health benefits [8][9][10][11] . Therefore, the encapsulation of PC may reduce these problems and enhance food products properties.…”
Section: Introductionmentioning
confidence: 99%
“…The low ability to inhibit XO with ILs results mainly from the properties of the acids used in their synthesis. Despite the high antioxidant activity, the activity of gallic acid towards the XO enzyme is described as low [72,73] . Studies by Honda et al.…”
Section: Resultsmentioning
confidence: 99%